Extracellular Enzyme of Endophytic Fungi Isolated from Ziziphus spina Leaves as Medicinal Plant - Sumaiya Naeema Hawar (International Journal of Biomaterials)
Endophytic fungi live inside plants or any part of them without creating any visible pathogenic signs. Endophytic fungi are found within medicinal plants and have shown strong biologic activity, such as anticancer and antioxidant activities, as well as producing extracellular enzymes. In this study, different fungal strains were isolated from the leaves of the medicinal plant Ziziphus spina, including Aspergillus flavus, Aspergillus fumigatus, Aspergillus niger, Cladosporium sp., Rhizopus sp., and Mucor sp. Extracellular enzymes have been quantified using agar plate-based methods in which fungi were grown in specified growth media to detect the enzymes produced. The results showed that A. niger has the highest ability to produce amylase, Cladosporium sp. has the highest ability to produce protease and pectinase, Rhizopus and Mucor sp. have the highest ability to produce cellulase, and A. niger and Cladosporium sp. have the same ability to produce lipase and laccase. The ability of medicinal plant endophytic fungi to produce extracellular enzymes has great therapeutic potential in clinical microbiology. Some of the isolates showed great activity in secreting particular enzymes, indicating that the enzymes of these fungi could be used in a variety of applications.